Edukasi Masyarakat tentang Sifat Termal Sampah dan Dampak Negatif Pembakaran Plastik terhadap Lingkungan dan Kesehatan (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Semarang City has experienced significant growth over the past five years (2020 – 2025). Rapid urban development has been positively correlated with increasing environmental burdens, particularly in solid waste generation. In Indonesia, the largest portion of municipal waste consists of food waste, followed by plastic waste. Among these, plastic waste is the most difficult to manage. It is estimated that around 70% of Indonesian households still burn their waste as a means of disposal. The burning of waste, especially plastics, releases toxic emissions such as dioxins, furans, and fine particulates, which pose serious health risks, particularly to the respiratory system. This practice not only worsens air quality but also threatens public health. This community service program focused on providing education about the thermal properties of waste and the negative impacts of plastic burning on both the environment and human health. The program aimed to improve public knowledge of the thermal characteristics of various types of waste and the hazards of plastic burning through accessible scientific outreach. The initiative is expected to raise awareness and understanding of environmentally friendly waste management alternatives such as waste separation, composting, and recycling. The activity was conducted in RW 01, Tugurejo Village, Tugu District, Semarang City.